2023
DOI: 10.3390/ma16041400
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cu Content on the Alloy Tensile Properties of Al-Cu Based Alloys Tested at 25 °C and 250 °C: Application of the Concept of Quality Index

Abstract: The present work was performed on three versions of a newly developed alloy coded T200 containing 6.5% Cu, 0.1% Fe, 0.45% Mg, and 0.18% Zr in addition to A319 and A356 alloys (grain refined and Sr-modified). Tensile bars were subjected to 13 different heat treatments prior to testing at either 25 °C or 250 °C. The tensile data were analyzed using the quality index method. The results obtained showed that, due to the high copper content in the T200 alloy coupled with proper grain refining, the alloy possesses t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…showed that 7075 alloy, 7075 alloy + Zr, or 7075 alloy + Sc + Zr alloys offer better mechanical properties caused by the precipitation of Al 3 (Sc, Zr) dispersoids [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…showed that 7075 alloy, 7075 alloy + Zr, or 7075 alloy + Sc + Zr alloys offer better mechanical properties caused by the precipitation of Al 3 (Sc, Zr) dispersoids [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%